Clinicians' Perceptions of Futile or Potentially Inappropriate Care and Associations with Avoidant Behaviors and Burnout - Chamberlin, Peter (J Palliat Med, 2019)
Background: Futile or potentially inappropriate care (futile/PIC) for dying inpatients leads to negative outcomes for patients and clinicians. In the setting of rising end-of-life health care costs and increasing physician burnout, it is important to understand the causes of futile/PIC, how it impacts on care and relates to burnout. Objectives: Examine causes of futile/PIC, determine whether clinicians report compensatory or avoidant behaviors as a result of such care and assess whether these behaviors are associated with burnout. Design: Online, cross-sectional questionnaire. Setting/Subjects: Clinicians at two academic hospitals in New York City. Methods: Respondents were asked the frequency with which they observed or provided futile/PIC and whether they demonstrated compensatory or avoidant behaviors as a result. A validated screen was used to assess burnout. Measurements: Descriptive statistics, odds ratios, linear regressions. Results: Surveys were completed by 349 subjects. A majority of clinicians (91.3%) felt they had provided or “possibly” provided futile/PIC in the past six months. The most frequent reason cited for PIC (61.0%) was the insistence of the patient's family. Both witnessing and providing PIC were statistically significantly (p < 0.05) associated with compensatory and avoidant behaviors, but more strongly associated with avoidant behaviors. Provision of PIC increased the likelihood of avoiding the patient's loved ones by a factor of 2.40 (1.82–3.19), avoiding the patient by a factor of 1.83 (1.32–2.55), and avoiding colleagues by a factor of 2.56 (1.57–4.20) (all p < 0.001). Avoiding the patient's loved ones (β = 0.55, SE = 0.12, p < 0.001), avoiding the patient (β = 0.38, SE = 0.17; p = 0.03), and avoiding colleagues (β = 0.78, SE = 0.28; p = 0.01) were significantly associated with burnout. Conclusions: Futile/PIC, provided or observed, is associated with avoidance of patients, families, and colleagues and those behaviors are associated with burnout.